Rural Poverty in Transition Countries - Karen Macours; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2006)
This paper uses new poverty data based on household level surveys to analyze changes in rural poverty and rural-urban poverty differences in 23 transition countries of Central and Eastern Europe and the firmer Soviet Union. The paper presents a series of hypotheses to explain differences across countries and changes over time.
Keywords: 330; rural poverty; transition; Eastern Europe; Former Soviet Union; Ländliche Armut; Agrarreform; Übergangswirtschaft; Osteuropa; Russland